Design and fabrication of a multipurpose baby cot - Roslan, Nabil Qayyum; Khairulmaini, Miqdad (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
The increasing demand for space-saving and multifunctional baby furniture has led to the development of a multipurpose baby cot, designed for household use and emergency situations such as floods. This project focuses on the design and fabrication of a modular baby cot that integrates convertibility, buoyancy for flood safety, and structural stability. The design process involved CAD modeling, material selection, and fabrication using lightweight yet durable materials to ensure strength and water resistance. Engineering analysis was conducted to assess load-bearing capacity, stability, and structural integrity under different conditions. Testing results showed that the cot remained stable while floating and maintained its balance under load. However, further improvements in waterproofing, weight distribution, and attachment mechanisms are recommended to enhance durability and long-term usability. This project demonstrates the feasibility of integrating modular and buoyant features into baby furniture, providing a practical and adaptable alternative for modern households and emergency relief applications.